Lifestyle and health related behaviors of middle school students from city and village schools - Ślaska, Natalia; Bartoszewska, Anna; Kaźmierczak, Arkadiusz; Robacha, Jadwiga (Biospołeczne uwarunkowania uczestnictwa w kulturze fizycznej i zdrowotnej osób w różnym wieku, 2017)
Health behaviors determine human health in the highest degree. Physical activity, balanced nutrition and avoidance of risky behaviors, such as smoking, alcohol abuse or unjustified slimming is a starting point to keep healthy for many years. Extremely important is creating health related behaviors in youth period, because then learned habits and behaviors are becoming established and find reflection in the next years of human life. The object of this thesis is an attempt to estimate the level of health related behaviors and lifestyle of middle school students from city and village schools.